A contra-hegemonia na formação de educadores do campo : uma análise sobre o curso de pedagogia da terra - Torres, Lianna de Melo (2012)
This study aims to investigate the pretension of the MST of forge a Pedagogy course in universities able to incorporate the popular struggle for land for the formation of ―organic intellectuals of the movement of the field‖, which should contribute to the construction of a popular education project, whose final goal was the individual and collective emancipation towards a new project for Brazil. Motivated by the need to face a depth reflection political-pedagogical, we seek transcending the appearance of the phenomena observed, to dive into their essence, investigating about the limits and possibilities of constructing a counter-hegemonic education in Pedagogy courses offered at public universities to the landless. We tread for a Marxian perspective of the analysis, electing as explanatory categories the totality and the contradiction. The empirical field is the work of pedagogues of the land in their communities, at the schools or Departments of Education, in the Education Sector of the MST, in defense of rural education and school articulated to "pedagogy of movement" in the agrarian reform settlements of Sergipe. We use as instruments for data collection the interview, the focal group and also we resorted to documentary sources. Understanding the relationship education-work as a basic category of construction of human emancipation we elected work as category analysis. The work in their multiple determinations, since work as an educational principle, claimed by social movements as central theme of the Pedagogy course, as work materialized in the action of the rural pedagogue, while produces the education of the field and reproduces its own survival. Somehow, it is possible to say, as a result, always partial, that this mismatch between universities and social movements, it was important from the standpoint political and pedagogical. If we do not produce a "new type of intellectual" at least we understand the possibilities that we must develop methodologies to that workers can approach the world of knowledge. Since Gramsci the knowledge must be a conquest which student is mobilized to do it. This mobilization is produced in the daily, in real life, in social practice, so it has a class character. Rural workers arrive to university mobilized by the political practice organizational of their movements, to the university would fit to invest in processes of knowledge acquisition through investigation-action as established in the critical currents of teacher training, methodological option capable of producing knowledge as revolutionary praxis.